Advances in droplet digital polymerase chain reaction on microfluidic chips. Issue 5 (8th February 2023) - Xu, Danfeng; Zhang, Weifei; Li, Hongmei; Li, Nan; Lin, Jin-Ming
Abstract : This graphic includes droplet generation methods, thermal cycle strategies, signal counting approaches, and the applications in the fields of single-cell analysis, disease diagnosis, bacteria detection, and virus detection. Abstract : The PCR technique has been known to the general public since the pandemic outbreak of COVID-19. This technique has progressed through three stages: from simple PCR to real-time fluorescence PCR to digital PCR. Among them, the microfluidic-based droplet digital PCR technique has attracted much attention and has been widely applied due to its advantages of high throughput, high sensitivity, low reagent consumption, low cross-contamination, and absolute quantification ability. In this review, we introduce various designs of microfluidic-based ddPCR developed within the last decade. The microfluidic-based droplet generation methods, thermal cycle strategies, and signal counting approaches are described, and the applications in the fields of single-cell analysis, disease diagnosis, and pathogen detection are introduced. Further, the challenges and prospects of microfluidic-based ddPCR are discussed. We hope that this review can contribute to the further development of the microfluidic-based ddPCR technique.